APPLICATION OF SPECIAL WORK EXCHANGE (BKK) INFORMATION SYSTEM BASED ON WEBSITE - Huda, Baenil; Tukino; Hamdani, Dani (International Journal of Psychosocial Rehabilitation, 2020)
Vocational High School 1 Cikampek is one of the vocational schools in Karawang Regency and the school has 7 engineering majors namely Mechanical Engineering, Automotive Mechanical Engineering, Electronic Engineering, Industrial Automation Engineering, Chemical Analysis Engineering, Electrical Engineering and Agribusiness. Vocational High School 1 Cikampek Already has a Special Work Exchange (BKK), which is a body that handles the problem of the distribution of graduates and job vacancies. But the delivery of BKK Vocational High School 1 Cikampek information is still by sticking to the announcement on the BKK announcement board when there are job vacancies information or test schedules and information from the company. This is a problem for alumni who are home away from school, or are already outside the area, and therefore very much needed a website BKK 1 Vocational High School Cikampek which can be accessed anywhere by alumni. The purpose of this study was to produce a website BKK Cikampek 1 Vocational High School that can be accessed anywhere by alumni. The benefits of this web-based information system is that it makes it easy to deliver work schedule information and test info from the company. Making this information system using the Php programming language with a MySQL database and display using Adobe Dreamweaver to make it more interesting. Making this BKK profile website is useful for BKK Cikampek Vocational High School 1 and alumni.